Racial disparity in the association between body mass index and self-reported asthma in children: a population-based study. (27th May 2016) - Joseph, Michael; Elliott, Michael; Zelicoff, Alan; Qian, Zhengmin; Trevathan, Edwin; Chang, Jen Jen
Abstract: Objective : To examine the racial disparity in the association between obesity and asthma in US children and adolescents. Methods : This study was based on a nationally representative, random-digit-dial sample of US households with children less than 18 years of age from the National Survey of Children's Health in 2011/2012 and 2007. The study sample included 88, 668 children ages 10–17 with data on body mass index (BMI), parental reporting of asthma diagnosis, and potential confounders. Multiple logistic regression analysis was performed to estimate the crude and adjusted odds ratios stratified by child race/ethnicity. Results : The prevalence of overweight was 15.2% and obesity was 14.1%. Self-reported asthma diagnosis was 16.7% in our study sample. Obese children were 51% more likely to have asthma compared to normal weight children after controlling for child's sex, child age, socioeconomic status, environmental tobacco smoke (ETS), and neighborhood conditions. Our study also shows that the strength of this association varied by race/ethnicity after stratification. Being male, being non-Hispanic Black or Multi-racial, below the Federal Poverty Level, ETS and having detracting neighborhood elements were also significantly associated with higher odds of having a self-reported asthma diagnosis. Conclusion : We observed a racial difference in the association between BMI and asthma in US children. Our findings have significant public health implications and may help public health practitioners to target children and adolescents at higher risk of prevention and intervention efforts.